The role of electroencephalography in the diagnosis of serotonin syndrome. (August 2016) - Krishnamoorthy, Theeba; Knighton, John; Merton, Louis
Serotonin syndrome is a potentially life-threatening side-effect of agents that enhance synaptic serotonin levels. With the increasing use of serotoninergic agents greater awareness of serotonin syndrome is necessary, including the potential for drug interactions with serotoninergic agents to produce serotonin syndrome. Clinical presentation ranges from mild reactions to a severe toxic state involving generalized tonic-clonic seizures, fevers exceeding 40℃ or coma. This case highlights the necessity of considering serotonin syndrome alongside other differential diagnoses: neuroleptic malignant syndrome, infectious cause, atypical seizures and delirium tremens, in the setting of altered mental state with abnormal neurology. It highlights the potential diagnostic use of electroencephalography in supporting a diagnosis of serotonin syndrome.